Comportamiento proambiental de los estudiantes de la Universidad Autónoma de Guerrero, México - Saldaña-Almazán, Mirella; Carrasco Urrutia, Katya Aimee; Maldonado-Astudillo, Yan P.; Sampedro-Rosas, María Laura; Rosas-Acevedo, José L.; Juárez-López, Ana L. (2020)
http://ojs.sociologia-alas.org/index.php/CyC/article/view/158